PELATIHAN ARTIFICIAL INTELLIGENCE UNTUK DETEKSI MOTIF BATIK BAGI GURU SMKN 3 MAGELANG - Himmah, Laila Nurul; Muslikhin, Muslikhin; Suharyadi , Aris (Abdi Seni, 2025)
ABSTRACT This community service was carried out at SMK Negeri 3 Magelang with the aim of growing teachers' interest in implementing artificial intelligence (AI) in the educational field of fashion design and multimedia. This training provides additional skills in simple programming oriented towards AI-based batik motif detection. The benefit of this activity is that teachers' perceptions of the development of AI are getting better, especially in the field of vocational education. The activity program provided is batik motif detection training using MATLAB software up to coding. This service activity program was carried out in the form of mentoring and training for 20 beneficiaries. The training was held in 2 meetings, starting with providing insight and demonstration of AI concept knowledge material and MATLAB software-based programming for batik motif detection, followed by practice by the participants. The method applied in this training activity is through lecture, demonstration and discussion methods. The results achieved in this activity were that the teacher participants at SMKN 3 Magelang gained insight and additional skills in the field of AI, especially in MATLAB software for detecting batik motifs.